Eye movements, convergence distance and pupil-size when reading from smartphone, computer, print and tablet - Miranda, Antonio Miguel; Nunes-Pereira, Eduardo J; Baskaran, Karthikeyan; Macedo, Antonio Filipe (Scandinavian Journal of Optometry and Visual Science, 2018)
This study investigated the use of eye-tracking glasses to monitor visual behaviour when reading from electronic devices and paper in free-viewing conditions. The Tobii-Pro-Glasses were used to monitor 20 subjects with normal vision during reading tasks. Reading was performed in a smartphone, computer, paper and tablet. Texts from the IReST-test were read in devices in a random order. Participants read one text in each device and then repeated the same task 1 hour later; in total each participant read eight different texts. The sequence for the devices was randomized. We found differences between devices for saccade amplitude, fixation duration, convergence distance and pupil size. Reading speed between computer and tablet was slightly different (8 words-per-minute) and pupil size reduced up to 20% in electronic devices compared to print. Behavioural changes observed whilst reading from different devices may reflect an attempt from readers to optimize performance. The need to maintain visual performance under different visual condition may lead to increased visual symptoms. Eye-tracking glasses could be a valuable tool to investigate visual aspects of digital strain.